Bamboo pulp treated with NaOH and benzophenone tetracarboxylic dianhydride as reinforcement of new polymerics materials. - Guimarães Júnior, Mário (2015)
Bamboo admittedly and engineering material widely used for buildings in several countries. However, lack of good interfacial adhesion, low melting point, and poor resistance towards moisture make the use of natural fiber reinforced composites less attractive. The aim of this work was esterify the refined pulp of bamboo came from kraft industrial pulping, previously treated with sodium hydroxid and organic solvents for the production of less hydrophilic materials. In order to verify the occurrence of reaction, assays of spectroscopy in the region of IV, thermogravimetry, elementary analysis and water absorption were performed. After the reaction, the infrared spectra presented bands related to the ester and carboxylic acid groups, evidencing the exchange of OH groups for ester groups. This test also shows a decrease in the absorbance ratio due to the presence of ester group causing a reduction in the crystallinity index of the sample. These results were proven by the gain in the value of carbon content after the elementary analysis. In the water absorption test, the pulp modified with dianhydride showed the lowest level as compared to other samples. The thermogravimetric analysis also showed a decrease in initial temperature of pulp degradation, as well as decrease in the moisture, facts that proved the efficiency in the modification using dianhidrido BTDA.